Coated steel sheet and high strength press hardened steel part and manufacturing method thereof

The development of a coated steel sheet with a specific composition and microstructure enables the production of press-hardened steel parts with high tensile strength and improved bending properties, overcoming the challenges faced by existing technologies.

JP7665755B2Active Publication Date: 2025-04-21ARCELORMITTAL SA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023536409
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-16
Filing Date
2021-12-03
Publication Date
2025-04-21
Estimated Expiration
2041-12-03

AI Technical Summary

Technical Problem

Existing press-hardened steel parts face challenges in achieving a combination of high tensile strength (1500 MPa or higher) and good bending properties (bending angle greater than 70°), while maintaining high mechanical properties and corrosion resistance.

Method used

A coated steel sheet with a specific composition and microstructure is developed, featuring a decarburizing layer with a ferrite layer of 20 μm to 100 μm thickness, a bulk with 60% to 90% ferrite, and an aluminum-based coating layer. The steel sheet is processed through hot rolling, cold rolling, and annealing to achieve the desired microstructure and properties.

Benefits of technology

The resulting press-hardened steel parts exhibit a tensile strength of 1500 MPa or higher and a bending angle greater than 70°, while maintaining high yield strength (1250 MPa or higher) and good corrosion resistance, thus addressing the limitations of existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665755000006
    Figure 0007665755000006
  • Figure 0007665755000007
    Figure 0007665755000007
  • Figure 0007665755000008
    Figure 0007665755000008
Patent Text Reader

Abstract

The present invention relates to a coated steel sheet and a press-hardened steel part having a composition, in weight percent, of 0.26-0.40% C, 0.5-1.8% Mn, 0.1-1.25% Si, 0.01-0.1% Al, 0.1-1.0% Cr, 0.01-0.1% Ti, 0.001-0.004% B, P≦0.020%, S≦0.010%, and N≦0.010%, with the remainder of the composition being iron and unavoidable impurities resulting from refining. The press-hardened steel part comprises a bulk having a microstructure containing, by surface fraction, more than 95% martensite and less than 5% bainite, a coating layer on the surface of the steel part, a ferrite interdiffusion layer between the coating layer and the bulk, and a composition represented by the following formula: (GW int / PAGS bulk )-1≧30% of the prior austenite grain size in the bulk. bulk Width of ferrite grains in the interdiffusion layer GW int Includes the ratio of
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to coated steel sheets and high strength press hardened steel parts having good bending properties. [Background technology]

[0002] The high strength press hardened parts may be used as structural elements in motor vehicles for anti-intrusion or energy absorbing functions.

[0003] For these types of applications, it is desirable to produce steel parts that combine high mechanical strength, high impact resistance and good corrosion resistance. Furthermore, one of the main challenges in the automotive industry is to reduce the weight of vehicles to improve their fuel efficiency in terms of protecting the global environment, without neglecting safety requirements.

[0004] This weight reduction can be achieved, inter alia, through the use of steel components with a martensite or bainitic / martensite microstructure.

[0005] The publication WO 2016104881 relates to a hot press formed part used as a structural part for vehicles and the like, which requires impact resistance properties, more specifically a tensile strength of 1300 MPa or more, and a manufacturing method, as well as a method of heating a steel material to a temperature at which austenite single phase can be formed, and quenching and hot forming using a die. To obtain such properties, the base steel sheet needs to include a thin ferrite layer of less than 50 μm on the surface, and to control the size and density of carbides. This ferrite layer in the substrate allows the suppression of the propagation of fine cracks formed on the plating layer to the base sheet, but results in poor bendability with a bending angle of less than 70°.

[0006] WO 2018179839 relates to a hot pressed part obtained by hot pressing a steel sheet having a microstructure varying through the thickness, comprising a soft layer made of at least 90% ferrite, a transition layer made of ferrite and martensite, and a hard layer mainly composed of martensite, the hot pressed part having both high strength and high bendability. To obtain such properties, the cold rolled steel sheet is annealed in an atmosphere with a dew point temperature of 50°C to 90°C, which may be detrimental to the aluminum alloy coating. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2016 / 104881 [Patent Document 2] International Publication No. 2018 / 179839 Summary of the Invention [Problem to be solved by the invention]

[0008] It is therefore an object of the present invention to solve the above mentioned problems and to provide a press hardened steel part having a combination of high mechanical properties with a tensile strength TS of 1500 MPa or more and a bending angle of more than 70°. Preferably, the press hardened steel part according to the present invention has a yield strength YS of 1250 MPa or more.

[0009] Another object of the present invention is to obtain a coated steel sheet which can be transformed into such press hardened steel parts by hot forming. [Means for solving the problem]

[0010] The object of the present invention is achieved by providing a steel sheet according to claim 1. A further object is achieved by providing a method according to claim 2. A further object of the present invention is achieved by providing a press hardened steel part according to claim 3. The steel part may also comprise the properties according to any one of claims 4 to 6. A further object is achieved by providing a method according to claim 7.

[0011] The invention will now be described in detail and illustrated by way of example, without introducing any limitations, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0012] [Figure 1a] FIG. 4 shows a schematic cross-section of a coated steel sheet from test 4, which is not according to the invention. [Figure 1b] FIG. 1 represents a schematic cross-section of a press hardened steel part from Test 4, which is not according to the present invention. [Figure 2a] FIG. 3 shows a schematic cross-section of a coated steel sheet from test 3, which is not according to the invention. [Figure 2b] FIG. 1 represents a schematic cross-section of a press hardened steel part from test 3, which is not according to the present invention. [Figure 3a] 1 shows a schematic cross-sectional view of a coated steel sheet of test 2, according to the present invention. [Figure 3b] FIG. 1 shows a schematic cross-section of a press hardened steel part from test 2 according to the present invention. [Figure 4a] FIG. 1 shows a schematic cross-sectional view of a coated steel sheet from test 1, according to the present invention. [Figure 4b] FIG. 1 shows a schematic cross-section of a press hardened steel part from test 1 according to the present invention. [Figure 5a] FIG. 5 shows a schematic cross-section of a coated steel sheet from test 5, which is not according to the invention. [Figure 5b] FIG. 1 represents a schematic cross-section of a press hardened steel part from Test 5, which is not according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The composition of the steel according to the invention will now be described, the contents being expressed in weight percent.

[0014] According to the present invention, the carbon content is 0.26%-0.40% to ensure satisfactory strength. If the carbon content exceeds 0.40%, the weldability and bendability of the steel plate may be reduced. If the carbon content is less than 0.26%, the tensile strength does not reach the target value.

[0015] The manganese content is in the range of 0.5% to 1.8%. If the amount of addition exceeds 1.8%, the risk of center segregation increases and the bendability is impaired. If the amount of addition is less than 0.5%, the hardenability of the steel sheet decreases. Preferably, the manganese content is in the range of 0.5% to 1.3%.

[0016] According to the present invention, the silicon content is comprised between 0.1% and 1.25%. Silicon is an element involved in hardening in solid solution. Silicon is added to limit the formation of carbides. Above 1.25%, silicon oxide is formed on the surface, impairing the coatability of the steel. Furthermore, the weldability of the steel sheet may be reduced. Preferably, the silicon content is between 0.2% and 1.25%. More preferably, the silicon content is between 0.3% and 1.25%. More preferably, the silicon content is between 0.3% and 1%.

[0017] The aluminum content is comprised between 0.01% and 0.1%, because it is a very effective element for deoxidizing steel in the liquid phase during refining. When the titanium content is not sufficient, aluminum can protect boron. The aluminum content is less than 0.1% to avoid oxidation problems and ferrite formation during press hardening. Preferably, the aluminum content is comprised between 0.01% and 0.05%.

[0018] According to the present invention, the chromium content is comprised between 0.1% and 1.0%. Chromium is an element involved in hardening in solid solution and should be higher than 0.1%. The chromium content is less than 1.0% to limit workability issues and costs.

[0019] The titanium content is included between 0.01% and 0.1% to protect boron from the formation of BN. The titanium content is limited to 0.1% to avoid TiN formation.

[0020] According to the invention, the boron content is comprised between 0.001% and 0.004%. Boron improves the hardenability of the steel. The boron content is not more than 0.004% in order to avoid the risk of the slab breaking during continuous casting.

[0021] Several elements can be optionally added.

[0022] Nickel can be added as an optional element up to a maximum of 0.5% since it can substantially reduce the sensitivity to delayed fracture.

[0023] Molybdenum content may be added at any time up to a maximum of 0.40%. Like boron, molybdenum improves the hardenability of the steel. Molybdenum is not more than 0.40% to limit costs.

[0024] According to the invention, niobium can be added optionally up to a maximum of 0.08% to improve the ductility of the steel. If the addition exceeds 0.08%, the risk of the formation of NbC or Nb(C,N) carbides increases, impairing the bendability. Preferably, the niobium content is equal to or less than 0.05%.

[0025] Calcium may also be added as an optional element up to a maximum of 0.1%. The addition of Ca at the liquid stage allows for the formation of fine oxides which promote castability in continuous casting.

[0026] The remainder of the steel composition is iron and impurities resulting from refining. In this respect, P, S and N are at least considered as residual elements, which are unavoidable impurities. Their contents are less than 0.010% for S, less than 0.020% for P and less than 0.010% for N.

[0027] Next, the microstructure of the coated steel sheet according to the present invention will be described.

[0028] The cross section of the coated steel sheet of the present invention is represented diagrammatically in Figures 3a and 4a. The coated steel sheet is covered on top with a decarburized layer (3) comprising a ferrite layer (4) having a thickness of 1 µm to 100 µm and comprises a coating layer (1) and a bulk (2). Preferably, the thickness of the ferrite layer is comprised between 20 µm and 100 µm. More preferably, the thickness of the ferrite layer is comprised between 25 µm and 100 µm. More preferably, the thickness of the ferrite layer is comprised between 30 µm and 80 µm.

[0029] The bulk (2) of the coated steel sheet has a microstructure containing 60% to 90% ferrite in terms of surface fraction, with the remainder being island martensite-austenite, pearlite or bainite.

[0030] This ferrite is formed during intercritical annealing of cold rolled steel sheet. The remainder of the microstructure, at the end of soaking, is austenite, which transforms to martensite-austenite islands, pearlite or bainite during cooling of the sheet.

[0031] The decarburized layer present at the top of the bulk is obtained during annealing of cold-rolled steel sheet by controlling the atmosphere in the furnace so as to set the dew point temperature strictly above -10°C and below 20°C.

[0032] The coated steel sheet according to the invention can be produced by any suitable production method, which the skilled person can define. However, it is preferable to use a method according to the invention comprising the following steps: The above-mentioned steel composition is provided to a semi-finished product which can be further hot rolled. The semi-finished product is reheated at a temperature in the range of 1150°C to 1300°C.

[0033] The steel sheet is then hot rolled at a finish hot rolling temperature in the range of 800°C to 950°C.

[0034] The hot rolled steel is then cooled and coiled at a temperature Tcoil below 670°C and optionally pickled to remove oxidation.

[0035] The coiled steel sheet is then optionally cold-rolled to obtain a cold-rolled steel sheet. The cold-rolling reduction is preferably comprised between 20% and 80%. If it is less than 20%, recrystallization during the subsequent heat treatment is not favorable, and the ductility of the steel sheet may be impaired. If it exceeds 80%, there is a risk of edge cracks occurring during cold rolling.

[0036] The steel sheet is then annealed at a temperature T in the range of 700°C to 850°C in an HNx atmosphere containing 0% to 15% H. A Anneal to 10 s to 1200 s, including holding time t A The annealing temperature T A The temperature is maintained at 700°C to obtain an annealed steel sheet. If the temperature is less than 700°C, the rate of formation of the decarburized layer is too slow, and it is not possible to obtain a ferrite layer on top of the decarburized layer. A is greater than or equal to 10 seconds to allow for the formation of a ferrite layer, and less than or equal to 1200 seconds to limit the thickness of this ferrite layer.

[0037] During this annealing, the atmosphere in the furnace must have a dew point temperature T strictly above -10 ° C and below +20 ° C in order to form the decarburized layer according to the invention. DP1 The control is performed so that T DP1 If the temperature is below -10℃, the formation of the decarburized layer will be slow and the ferrite layer will not form on top of it. The bendability of the steel parts will be too low. DP1 If the temperature is higher than 20°C, the surface of the steel sheet may be completely oxidized, which may impair the coating property and mechanical properties of the steel sheet.

[0038] In one embodiment of the present invention, the annealed steel sheet is heated to an annealing temperature T2 comprised between 700°C and 850°C and maintained at said temperature T2 for a holding time t2 comprised between 10 seconds and 1200 seconds, and the atmosphere is kept at a dew point T2 strictly between -10°C and +20°C. DP2 has.

[0039] The steel sheet is then coated with an aluminum alloy coating.

[0040] The microstructure of a press-hardened steel part according to the invention will now be described: A cross-section of a press-hardened steel part is represented diagrammatically in Figures 3b and 4b.

[0041] The steel parts are continuously subjected to the following from the bulk to the surface of the steel parts: - a bulk having a microstructure containing more than 95% martensite and less than 5% bainite at the surface fraction (7); - ferrite interdiffusion layer (6), -aluminum-based coating layer (5) Includes.

[0042] During heating of the steel blank cut from the steel plate according to the invention, all microstructural elements of the bulk are transformed into austenite, and the ferrite of the decarburized layer is transformed into austenite with a grain size wider than that of the bulk. After hot forming, the steel part is then die quenched. The interdiffusion layer has a grain width larger than the prior austenite grain size in the bulk, since it grows from the former broad-grained austenite layer. In order to improve the bendability of the steel plate without reducing the mechanical properties, the prior austenite grain size in the bulk is reduced by PAGS. bulk Width of ferrite grains in the interdiffusion layer GW int The ratio is given by the following formula: (GW int / PAGS bulk )-1≧30% Meet the following.

[0043] This is to improve the bending workability of the steel sheet without deteriorating the mechanical properties. The width of the ferrite grain is the average distance between two parallel grain boundaries of the interdiffusion layer, and the grain boundaries are oriented in the thickness direction of the steel sheet. The annealing temperature T A , annealing time t A and dew point temperature T DP1 The combination of these two factors results in a large grain width GW in the interdiffusion layer. intFurthermore, heat treatment of the steel blank prior to press forming controls the austenite grain growth and therefore the PAGS in the bulk.

[0044] In one embodiment, the press hardened steel part may further include a martensite layer with a carbon gradient between the bulk and the interdiffusion layer, as represented by (8) in FIG. 4b. During heating of the steel blank, carbon diffuses from the bulk to the surface. The ferrite top of the decarburized layer then transforms into a layer of austenite with a carbon gradient. During die quenching, this austenite layer with a carbon gradient transforms into a layer of martensite with a carbon gradient.

[0045] The press-hardened steel parts according to the invention have a tensile strength TS of 1500 MPa or more and a bending angle of more than 70°. The bending angle is determined in the press-hardened parts according to the VDA 238-100 bending standard (normalized to a thickness of 1.5 mm).

[0046] In a preferred embodiment of the invention, the yield strength YS is greater than or equal to 1250 MPa. TS and YS are measured according to ISO standard ISO 6892-1.

[0047] The press hardened steel parts according to the invention can be manufactured by any suitable manufacturing method, which the skilled person can define. However, it is preferable to use a method according to the invention comprising the following steps: The coated steel sheet according to the present invention is cut to a predetermined shape to obtain a steel blank. The steel blank is then heated to a temperature comprised between 880°C and 950°C for 10 seconds to 900 seconds to obtain a heated steel blank. The heated blank is then transferred to a forming press before being hot formed and die quenched.

[0048] The invention will now be illustrated by the following examples, which are not intended to be limiting in any way. EXAMPLES

[0049] Six grades, whose compositions are summarized in Table 1, were cast into semi-finished products and processed into steel plates and then steel parts according to the processing parameters summarized in Table 2.

[0050] Table 1 - Composition The compositions tested are summarized in the table below, with elemental contents expressed as weight percent.

[0051] [Table 1]

[0052] Table 2 - Processing parameters The cast steel semi-finished products were reheated at 1200 °C, hot rolled at a finish hot rolling temperature including 800-950 °C, coiled at 550 °C, and cold rolled with a reduction of 60%. Then, the steel sheets were cooled to a temperature T A and held in an HNx atmosphere containing 5% H2 with a controlled dew point for a holding time of t A The steel sheet was then cooled to a temperature of 560-700° C. and then hot-dip coated with an aluminum-silicon coating containing 10% silicon.

[0053] Samples 1, 2, 5 and 6 were subjected to a second annealing at a temperature T2 before coating, at which the steel sheets were maintained for a holding time t2 in an HNx atmosphere with 5% H2 and controlled dew point. The following specific conditions were applied:

[0054] [Table 2]

[0055] The coated steel sheets were analyzed and the corresponding properties of the decarburized layer are summarized in Table 3.

[0056] Table 3 - Characteristics of the decarburized layer of coated steel sheets

[0057] [Table 3]

[0058] The coated steel plate was then cut to obtain steel blanks, which were then heated at 900 °C for 6 min and hot formed. The steel parts were analyzed to determine the corresponding microstructures, the width of the ferrite grains in the interdiffusion layer (GW) and the thickness of the interdiffusion layer (W). int and prior austenite grain size in the bulk PAGS bulk are summarized in Table 4. The mechanical properties are summarized in Table 5.

[0059] Table 4 - Microstructure of press hardened steel parts

[0060] [Table 4]

[0061] The surface fraction, the width of the ferrite grains in the interdiffusion layer and the PAGS are determined by the following method: a specimen is cut from the press-hardened steel part, polished and etched with reagents known per se to reveal the microstructure, and then the cross section is examined using an optical microscope or a scanning electron microscope, for example a scanning electron microscope equipped with a field emission electron gun ("FEG-SEM") with a magnification of more than 5000 times combined with a BSE (backscattered electron) device.

[0062] Table 5 - Mechanical properties of press hardened steel parts The mechanical properties of the tested samples were measured and are summarized in the following table:

[0063] [Table 5]

[0064] The examples show that the steel parts according to the invention, i.e. Examples 1-2, are the only steel parts that exhibit all the target properties thanks to their specific composition and microstructure.

[0065] FIG. 3a shows a schematic cross-sectional view of the coated steel sheet of Test 2. A , annealing time t A and dew point temperature T DP1This combination makes it possible to obtain a decarburized layer (3) on top of which a layer of ferrite (4) is formed.

[0066] The coated steel sheet is then hot formed. Figure 3b represents a schematic cross-section of the press-hardened steel part of test 2.

[0067] The grain width of the ferrite formed in the interdiffusion layer (5) is a legacy of the pure ferrite layer where austenite formation occurs during heating and has a larger grain size. The interdiffusion layer grows with this larger austenite grain size. The grain width of the ferrite in the interdiffusion layer (6) is larger than the prior austenite grain size in the bulk (7), resulting in good bendability with a bend angle of greater than 70°.

[0068] FIG. 4a shows a schematic cross-sectional view of the coated steel sheet of Test 1. A , annealing time t A and dew point temperature T DP1 This combination makes it possible to obtain a decarburized layer (3) thicker than in test 1 due to the higher C content, with a layer of ferrite formed on top (4).

[0069] The coated steel sheet is then hot formed. Figure 4b represents a schematic cross-section of the press-hardened steel part of test 1.

[0070] The grain width of the ferrite formed in the interdiffusion layer (6) is a legacy of the pure ferrite layer where austenite formation occurs during heating and has a larger grain size. The interdiffusion layer grows with this larger austenite grain size. The grain width of the ferrite in the interdiffusion layer (6) is larger than the prior austenite grain size in the bulk (7), resulting in good bendability with a bending angle of more than 70°. Furthermore, due to the thick ferrite layer (4) in the coated steel sheet, a layer of martensite with a carbon gradient forms between the bulk and the interdiffusion layer in the press hardened steel part, resulting in a tensile strength higher than 1500 MPa.

[0071] In test 3, the coated steel sheet has a decarburized layer without a ferrite layer on top of it, as shown diagrammatically in Fig. 2a. The absence of the ferrite layer is due to the low dew point temperature T of −10 °C. DP1 This is due to the fact that the rate of decarburization is slower.

[0072] The coated steel sheet is then hot formed. Figure 2b represents a schematic cross-section of the press-hardened steel part from test 3. Due to the absence of a ferrite layer, the width of the ferrite grains in the interdiffusion layer (6) is comparable to the prior austenite grain size in the bulk (7), resulting in a low bending angle of less than 70°.

[0073] In test 4, a low dew point temperature T of -40°C was used. DP1 This suggests that there is no decarburized layer or ferrite layer in the coated steel sheet.

[0074] FIG. 1a represents a schematic cross-section of the coated steel sheet of this test, with the coating layer (1) and the bulk (2).

[0075] The coated steel sheet is then hot formed. Figure 1b represents a schematic cross-section of the press-hardened steel part from test 4. Due to the absence of a ferrite layer, the width of the ferrite grains in the interdiffusion layer (6) is comparable to the prior austenite grain size in the bulk (7), resulting in a low bending angle of less than 70°.

[0076] In Test 5, the steel plate was kept at the soaking temperature for 10800 seconds, which resulted in the coated steel plate forming a thicker ferrite layer in the decarburized layer than in the previous tests. Figure 5a shows a schematic cross-section of the coated steel plate in Test 5, with the coating layer (1), the decarburized layer (3), a thicker ferrite layer with coarser grain size (4) and the bulk (2).

[0077] The coated steel sheet was then hot formed and Figure 5b represents a schematic cross-section of the press-hardened steel part from Test 5. During heating of the steel part, the bulk microstructure is austenitic and the thick ferrite layer transforms into a layer of austenite with a carbon gradient. However, for ferrite layer thicknesses greater than 100 μm, a layer of ferrite remains between the interdiffusion layer and the layer of austenite with a carbon gradient.

[0078] During die quenching of steel parts, the ferrite layer still exists and the austenite layer with carbon gradient transforms into a martensite layer with carbon gradient, resulting in a multiphase layer. This causes a reduction in yield strength.

[0079] In test 6, the steel sheet has a low carbon level of 0.21%. This low carbon content, combined with the processing parameters, results in a decarburized layer of the coated steel sheet with a ferrite layer. Nevertheless, the yield strength and tensile strength of the press-hardened steel part are not achieved due to the low carbon level.

Claims

1. The following, in mass percent: C: 0.26-0.40% Mn: 0.5-1.8% Si: 0.1-1.25% Al: 0.01~0.1% Cr: 0.1-1.0% Ti: 0.01~0.1% B: 0.001-0.004% P≦0.020% S≦0.010% N≦0.010% Including, and optionally, in weight percent, Ni≦0.5% Mo≦0.40% Nb≦0.08% Ca≦0.1% containing one or more of the elements A coated steel sheet made of a steel having a composition, The remainder of the composition is iron and inevitable impurities resulting from smelting, The coated steel sheet has a thickness of 1000 nm or less from the bulk to the surface of the coated steel sheet. - a bulk with a microstructure containing 60% to 90% surface fraction of ferrite, the remainder being islands of martensite-austenite, pearlite or bainite; - the bulk is covered with a decarburized layer on top, which includes a ferrite layer having a thickness between 1 μm and 100 μm, - a coating layer made of aluminium or an aluminium alloy Including, The coated steel sheet can be transformed by hot forming into a press-hardened steel part having a tensile strength TS of 1500 MPa or more and a bending angle of more than 70°, where the bending angle is determined in the press-hardened part according to the VDA 238-100 bending standard (normalized to a thickness of 1.5 mm); Coated steel sheet.

2. A method for producing the coated steel sheet according to claim 1, comprising: The following successive steps: - casting a steel having the composition according to claim 1 to obtain a slab, - the slab is subjected to a temperature T inclusive of 1100°C to 1300°C reheat reheating with hot rolling the reheated slab at a finish hot rolling temperature comprised between -800°C and 950°C; Winding temperature T below −670° C. coil coiling the hot-rolled steel sheet to obtain a coiled steel sheet; - optionally pickling the coiled steel sheet, - optionally cold rolling the coiled steel sheet to obtain a cold rolled steel sheet; - Hot-rolled or cold-rolled steel sheet is annealed at a temperature T of 700 ° C to 850 ° C. A and holding time t A The steel sheet is heated to the temperature T A to obtain an annealed steel sheet, the atmosphere containing 0% to 15% H2 and having a dew point T strictly higher than -10°C and lower than +20°C. DP1 having the steps of: - cooling the annealed steel sheet to a temperature range of 560°C to 700°C; - coating the annealed steel sheet with an aluminium or aluminium alloy coating, - cooling the coated steel sheet to room temperature; A method comprising:

3. A press hardened steel part comprising, in mass percent: C: 0.26-0.40% Mn: 0.5-1.8% Si: 0.1-1.25% Al: 0.01~0.1% Cr: 0.1-1.0% Ti: 0.01~0.1% B: 0.001-0.004% P≦0.020% S≦0.010% N≦0.010% Including, and optionally, in weight percent, Ni≦0.5% Mo≦0.40% Nb≦0.08% Ca≦0.1% Contains one or more of the elements having a composition The remainder of the composition is iron and inevitable impurities resulting from smelting, The steel part is continuously subjected to the following steps from the bulk to the surface of the steel part: - a bulk with a microstructure containing more than 95% martensite and less than 5% bainite at the surface fraction; - ferrite interdiffusion layer, - an aluminium-based coating layer, Including, Prior austenite grain size in the bulk PAGS bulk The width GW of the ferrite grains in the interdiffusion layer int The ratio of (GW int / PAGS bulk )-1≧0.3 Fulfilling The press-hardened steel part has a tensile strength TS of 1500 MPa or more and a bending angle of 70° or more, where the bending angle is determined in the press-hardened part according to the VDA 238-100 bending standard (normalized to a thickness of 1.5 mm); Press hardened steel parts.

4. 4. The press hardened steel part of claim 3 including a layer of martensite having a carbon gradient between the bulk and the ferrite interdiffused layer.

5. 5. Press hardened steel part according to claim 3 or 4, having a yield strength YS of 1250 MPa or more.

6. A method for manufacturing a press hardened steel part according to any one of claims 3 to 5, comprising the following successive steps: - providing a steel sheet having a composition according to claim 1 or produced by the method according to claim 2, - cutting said steel sheet into a predetermined shape to obtain a steel blank, - heating the steel blank to a temperature comprised between 880°C and 950°C for 10 seconds to 900 seconds to obtain a heated steel blank; - transferring the heated blank into a forming press; - hot forming the heated blank in said forming press to obtain a formed part, - die quenching the molded part; A method comprising:

Citation Information

Patent Citations

  • Method for producing plated steel sheet for hot press

    JP2006037130A

  • Plated steel sheet for hot press having excellent delayed fracture resistance, and method for producing the same

    JP2012041597A

  • Method for manufacturing a press-hardened coated steel part and a pre-coated steel sheet enabling the manufacture of such part

    JP2016504488A

  • Method for producing a steel sheet for press hardening, and component obtained by said method

    JP2017525849A

  • Method for producing high strength steel parts with improved ductility and parts obtained by said method

    JP2020522614A